Implementation of Mobile Ad-Hoc Network Using BATMAN Routing Protocol (Better Approach To Mobile Ad-hoc Network) for Salinity Monitoring in Vaname Shrimp Farms - Fadila Larasati; Nugroho Suharto; Aad hariyadi (Politeknik Negeri Malang, 2023)
Salinity is the key parameters in the shrimp culture environment. Conventional method is by visiting each pond plot. But,due to the large number and distance between the plots, this method is less effective. This ineffectiveness can lead to less than optimal yields. Manet is applied to increase the effectiveness of checking salinity using the BATMAN routing protocol. In this study, 2 units of laptops were used that act as Node 1 and Node 4, 2 units of Orange Pi Zero as Node 2, and 3. Each device is connected to a conductivity sensor to measure the salinity. The four devices are configured with an adhoc network using the BATMAN routing protocol. This research was conducted to provide an alternative for monitoring salinity to make it more effective. Based on the results of testing and analysis of network quality, the average delay value is 22.285 ms. The low delay value affects the percentage of packet loss in the four test scenarios with an average percentage of 0.999759613 %. Memory and CPU usage in testing 4 transition scenarios resulted in an average memory usage of 0.225% and CPU usage of 0.725%. The BATMAN routing protocol does not use a lot of memory and CPU usage because it only forwards data packets without the need to process data. From these data, it can be concluded that manet with batman routing protocol can be used as an alternative communication to provide communication network services in areas where there is no fixed network infrastructure.